National performance versus population at the Olympic Games: A methodology for determining elite performers - Putt, G. D. (International Journal of Sports Science, 2013)
The Summer Olympic Games always arouse great international interest and subsequent comment from national media, sports analysts and administrators on how its nation performed, often in relation to its population size. These determinations are usually based on gold medal tally and previous Olympic results rather than a sober quantitative analysis of overall medal tally. This happens because the official IOC medal table published is hierarchical, based primarily on gold medal winning tally. Inevitably, this table highlights achievement of the `superpower` countries but obscures extraordinary achievement by smaller countries. While the IOC table ranking can be indicative of relative comparative achievement between two countries of similar population size, it is nevertheless useless for indicating the relative quality of performance for those countries that differ in population size by factors of a thousand like The Bahamas and the USA. This study develops a quantitative metric that enables rational comparisons to be made between the performances of countries despite their population size. It does so using respective national populations and appropriately weighted medal tallies to develop an empirical power law refinement technique that determines the criterion for elite performance appropriate to a nation`s population.